RANCANG PEMBARUAN FRONT-END COMPANY PROFILE BERBASIS WEBSITE UNTUK PT. GERBANG SINERGI PRIMA - Nurazizah, Fahira; Komalasari, Rita (Jurnal informasi dan komputer, 2024)
PT. Gerbang Sinergi Prima is a part of the Pension Fund company PT. PLN (Persero), which focuses on the Information and Communication Technology (ICT) sector. Every company nowadays must have a company profile website, which serves not only as an investment but also a crucial necessity in this digital era. Therefore, a company profile website was built to serve as an information hub, branding platform, and online marketing tool. However, the current website design has been in use for quite some time, necessitating a redesign or update to provide visitors with a fresh look and new features aimed at enhancing aesthetics and improving website functionality, making it user-friendly. Extreme Programming (XP) falls under the category of popular agile methodologies, often applied in small-scale software development projects. This section on results and discussion is designed to present the outcomes of the research conducted. It is crafted in accordance with the Extreme Programming (XP) methodology, which includes planning, design, coding, and testing activities. From the results of this research, it can be concluded that the "Redesign of Front-End Company Profile Website" has been successfully developed to assist the work of PT. Gerbang Sinergi Prima in updating the company profile website in terms of its appearance. This research utilized the Extreme Programming methodology, chosen for its ability to accelerate and improve the efficiency of the system development process.